In the Sarmatian theater of (non)daily life - Patrycja Bąkowska (Przestrzenie Teorii)
The main purpose of this article is to show Old Polish literature and culture with regard to their performative aspects. By referring to Richard Schechner’s reflections, the author presents the Old Polish period “as a performance”. She focuses on issues such as time, space and behavior, which allows us to notice those activities of nobles that led to the formation of their personal and collective identity. An analysis of poems and diaries reveals different ways of creating one’s “self”. Various gestures and ceremonies as well as the skills that nobles developed through school education and socialization processes unified the Old Polish society, even though it was ethnically and religiously diverse.